The Biofilm Lifestyle Involves an Increase in Bacterial Membrane Saturated Fatty Acids - Dubois-Brissonnet, Florence; Trotier, Elsa; Briandet, Romain (Frontiers in Microbiology, 2016)
Biofilm formation on contact surfaces contributes to persistence of foodborne pathogens all along the food and feed chain. The specific physiological features of bacterial cells embedded in biofilms contribute to their high tolerance to environmental stresses, including the action of antimicrobial compounds. As membrane lipid adaptation is a vital facet of bacterial response when cells are submitted to harsh or unstable conditions, we focused here on membrane fatty acid composition of biofilm cells as compared to their free-growing counterparts. Pathogenic bacteria (Staphylococcus aureus, Listeria monocytogenes, Pseudomonas aeruginosa, Salmonella Typhimurium) were cultivated in planktonic or biofilm states and membrane fatty acid analyses were performed on whole cells in both conditions. The percentage of saturated fatty acids increases in biofilm cells in all cases, with a concomitant decrease of branched-chain fatty acids for Gram-positive bacteria, or with a decrease in the sum of other fatty acids for Gram-negative bacteria. We propose that decreased membrane fluidity in biofilm cells is an adaptive stress response that allows bacteria to limit exchanges, save energy and survive. Reprogramming of membrane fluidity in biofilms might explain specific biofilm behavior including bacterial recalcitrance to biocide action.